Surgical Site Infection After Primary Hip and Knee Arthroplasty: A Cohort Study Using a Hospital Database. (8th July 2015) - Grammatico-Guillon, Leslie; Baron, Sabine; Rosset, Philippe; Gaborit, Christophe; Bernard, Louis; Rusch, Emmanuel; Astagneau, Pascal
Abstract : BACKGROUND: Hip or knee arthroplasty infection (HKAI) leads to heavy medical consequences even if rare. OBJECTIVE: To assess the routine use of a hospital discharge detection algorithm of prosthetic joint infection as a novel additional tool for surveillance. METHODS: A historic 5-year cohort study was built using a hospital database of people undergoing a first hip or knee arthroplasty in 1 French region (2.5 million inhabitants, 39 private and public hospitals): 32, 678 patients with arthroplasty code plus corresponding prosthetic material code were tagged. HKAI occurrence was then tracked in the follow-up on the basis of a previously validated algorithm using International Statistical Classification of Disease, Tenth Revision, codes as well as the surgical procedures coded. HKAI density incidence was estimated during the follow-up (up to 4 years after surgery); risk factors were analyzed using Cox regression. RESULTS: A total of 604 HKAI patients were identified: 1-year HKAI incidence was1.31%, and density incidence was 2.2/100 person-years in hip and 2.5/100 person-years in knee. HKAI occurred within the first 30 days after surgery for 30% but more than 1 year after replacement for 29%. Patients aged 75 years or older, male, or having liver diseases, alcohol abuse, or ulcer sore had higher risk of infection. The inpatient case fatality in HKAI patients was 11.4%. CONCLUSIONS: The hospital database method used to measure occurrence and risk factors of prosthetic joint infection helped to survey HKAI and could optimize healthcare delivery. Infect Control Hosp Epidemiol 2015;36(10):1198–1207